Critical Connections: Health and Academics. (November 2015) - Michael, Shannon L.; Merlo, Caitlin L.; Basch, Charles E.; Wentzel, Kathryn R.; Wechsler, Howell
ABSTRACT BACKGROUND While it is a national priority to support the health and education of students, these sectors must better align, integrate, and collaborate to achieve this priority. This article summarizes the literature on the connection between health and academic achievement using the Whole School, Whole Community, and Whole Child (WSCC) framework as a way to address health‐related barriers to learning. METHODS A literature review was conducted on the association between student health and academic achievement. RESULTS Most of the evidence examined the association between student health behaviors and academic achievement, with physical activity having the most published studies and consistent findings. The evidence supports the need for school health services by demonstrating the association between chronic conditions and decreased achievement. Safe and positive school environments were associated with improved health behaviors and achievement. Engaging families and community members in schools also had a positive effect on students' health and achievement. CONCLUSIONS Schools can improve the health and learning of students by supporting opportunities to learn about and practice healthy behaviors, providing school health services, creating safe and positive school environments, and engaging families and community. This evidence supports WSCC as a potential framework for achieving national educational and health goals.